2018
DOI: 10.21615/cesp.11.1.4
|View full text |Cite
|
Sign up to set email alerts
|

Life Satisfaction in Chilean University Students: An Examination of the Relation between Gender and Socioeconomic Level

Abstract: The objectives of this study were to examine the psychometric properties of the Multidimensional Life Satisfaction Scale in university students (MSLSS) (Huebner, 1998) in a sample of university students from northern, central and southern Chile, where indicators of reliability and construct validity were examined. Also, it seeks to describe the levels of life satisfaction of students and to examine differences between gender and between socioeconomic statuses. The study is quantitative with a cross-sectional d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 41 publications
1
4
0
2
Order By: Relevance
“…Despite the evidence reported, it is necessary to point out that these results are conditioned by the characteristics of the sample and the structure of the test, as there are more women than men in this sample. However, these results are consistent with other studies [28] that have shown that women tend to suffer more depressive states because they generally perceive problems and adverse situations more intensely, with pessimistic thinking habits prevailing.…”
Section: Discussionsupporting
confidence: 92%
“…Despite the evidence reported, it is necessary to point out that these results are conditioned by the characteristics of the sample and the structure of the test, as there are more women than men in this sample. However, these results are consistent with other studies [28] that have shown that women tend to suffer more depressive states because they generally perceive problems and adverse situations more intensely, with pessimistic thinking habits prevailing.…”
Section: Discussionsupporting
confidence: 92%
“…In recent years, research on quality of life has broadened its focus to the measurement of life satisfaction (Denegri Coria et al, 2018). Also, life satisfaction is at the core of young adults' optimal functioning (Proctor et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…However, recent studies have taken this issue further. In this same vein, Denegri Coria et al (2018) carried out an analysis with a University sample in Chile to measure satisfaction with life in four dimensions: overall, family and friends, context (neighborhood and University) and self satisfaction. The results these researchers obtained showed significant differences in gender.…”
Section: Discussionmentioning
confidence: 99%